Confining a non-negative solution between a lower and upper solution for a sixth-degree boundary value problem - Bekri, Zouaoui; Fabiano, Nicola; Samei, Mohammad Esmael; Radenović, Stojan (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The aim of the paper is to prove the existence of solutions for a special case of the sixth-order boundary value problem.Methods: The Leray-Schauder fixed point theorem is used in order to determine lower and upper bound solutions.Results: Lower and upper bound solutions have been found.Conclusions: The sixth-order boundary value problem admits solutions.
Keywords: Leray-Schauder nonlinear alternative; Green’s function; fixed point theorem; lower and upper solutions; boundary value problem